Effect of purple yam (Dioscorea alata) on the degree and rate of tooth movement in guinnea pigs - Gumawid, Alphon Andrew S.
Purple yam has recently been researched for possible treatment and benefits for patients diagnosed with osteoporosis. It is believed to contain phytoestrogenic compounds that may have the ability to inhibit PTH-induced bone resorption and osteoclastic activity. The present study determined the effect of purple yam on the degree and rate of orthodontic tooth movement through diet modification of guinea pigs. For three weeks, a 1-mm activated orthodontic open coil spring was bonded to the incisor and the first molar of 16 guinea pigs, which were randomly divided into two groups. The test group received 750 mg/kg purple yam via syringe dosing, while the control group was given guinea pig pellets only. Each week following installation of the appliance, the weight of the guinea pigs and the degree and the rate of orthodontic tooth movement were measured and monitored. After the third week, all of the guinea pigs were sacrificed to determine histologically the effect of purple yam on inhibition of osteoclast formation. The results showed that there was no statistical difference both on the weight of the test subjects and on the degree of orthodontic tooth movement between the two groups. However, clinically the purple yam group demonstrated only 90% closure of the open coil spring, while the control group had total (100%) closure of the 1-mm activation. A significant difference on the rate of tooth movement between the two groups was seen only after the first week of appliance activation. Histologic examination revealed significantly less osteoclast count with the purple yam group. With the results obtained, purple yam has shown to have affected delay in orthodontic tooth movement attributed to inhibition of osteoclastic activity.